An EMI‐Optimized Transformer for De‐Y Flyback Converter with Low Common‐Mode Noise. Issue 8 (11th June 2021) - Wang, Tingying; Shao, Chensheng; Liu, Qi; Liao, Liangchuang; Qian, Qinsong; Ding, Desheng
Abstract : Y‐capacitors are widely used in flyback converters to suppress common‐mode (CM) noise to comply with the strict electromagnetic interference (EMI) standards. However, Y‐capacitors increase the leakage current between the primary and secondary side, which is not allowed in the applications with high safety requirements. In this paper, the displacement current models of two conventional De‐Y methods are quantitatively established to analyze their limitations for the flyback converter. Then, a hybrid EMI‐optimized transformer is proposed to improve the limitations. The proposed structure can completely balance the CM noise between the primary and secondary sides, making the flyback converter comply with the EMI standard under the conditions of no Y‐capacitor. Compared with the traditional methods, the proposed method has a better capability for CM noise suppression, higher universality and the same cost. Finally, the simulation and experimental results verify that the CM noise of the new transformer structure decreases about 10 dB compared with that of the conventional one. © 2021 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.